Value Chain and Added Value in Goat Milk-Based Enterprise: A Case Study of Kefir Jember - Ningsih, Yuni Dwi Puspita; Eka Putra, Dhanang (Journal of Supply Chain and Entrepreneurship, 2025)
Aim: This study aims to analyze the value chain and measure the added value generated by a small-scale goat milk processing enterprise (Kefir Jember) in producing goat milk kefir drinks and kefir facial masks.Method: A descriptive quantitative method was applied, using value chain analysis and the modified Hayami method to evaluate the economic contributions of primary and supporting activities. Data collection involved direct observation, structured interviews with open-ended questionnaires, and analysis of production and financial records.Findings: The findings reveal that Kefir Jember successfully integrates key primary activities, such as sourcing, production, and marketing, along with supporting activities including infrastructure, human resource training, and simple technology use. The added value calculation demonstrated significant profitability, especially for kefir facial masks, which generated substantially higher added value compared to kefir drinks. These results highlight the economic benefits of diversifying goat milk products into innovative health and cosmetic items.Significance: The study provides valuable insights for micro-scale agro-enterprises on how strategic value chain management and product diversification can significantly enhance profitability. Practically, these findings could guide similar small-scale businesses in improving operational efficiency, product competitiveness, and sustainable economic growth.